ADMINISTRATIVE AND TAX PRINCIPLES: A COMPARATIVE ANALYSIS FROM A HUNGARIAN PERSPECTIVE - Bobonka, Miklós Kornél (International Journal of Legal and Social Order, 2025)
Since the separation of general administrative and tax administration procedures in Hungary, fundamental principles have been given particular emphasis in all areas. Although the General Administrative Procedure Act aimed to streamline processes and reduce the volume of regulations, it nevertheless placed significant importance on these principles, some of which are derived directly from the Fundamental Law of Hungary. The entire tax administration procedure is also permeated by an emphasis on these principles. This study compares the fundamental principles of the two areas. To this end, it first presents the general functions and common theoretical framework of the principles, then systematically examines the principles of both procedural regimes and finally draws conclusions from the comparison.